SPE Reservoir Simulation Symposium 2011
DOI: 10.2118/141796-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Criteria for Dynamic Gridding during Reservoir Simulation of Water Flooding and Solvent Injection

Abstract: Some hydrocarbon recovery processes are characterized by the existence of sharp saturation and/or concentration fronts. Examples of such processes are VAPEX, in situ combustion, or water flooding of heavy oil reservoirs in presence of viscous fingering. In order to simulate correctly what happens around the fronts, small grid sizes need to be used. If however the whole reservoir is gridded very finely, computational time becomes prohibitive. In order to circumvent this problem, dynamic gridding, also callled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…7) are the coarse-scale transmissibilities in the buoyant and capillary terms. Any upscaling technique that yields coarse-block permeabilities or coarse-interface transmissibilities (Christie 1996;Farmer 2002;Barker and Thibeau 2007;Lie 2019) should be suitable. Herein, we use a simple and robust strategy that first upscales block permeabilities by harmonic averaging:…”
Section: Dynamic Coarseningmentioning
confidence: 99%
See 1 more Smart Citation
“…7) are the coarse-scale transmissibilities in the buoyant and capillary terms. Any upscaling technique that yields coarse-block permeabilities or coarse-interface transmissibilities (Christie 1996;Farmer 2002;Barker and Thibeau 2007;Lie 2019) should be suitable. Herein, we use a simple and robust strategy that first upscales block permeabilities by harmonic averaging:…”
Section: Dynamic Coarseningmentioning
confidence: 99%
“…More complex cases involving compositional simulations have been demonstrated for an early version of the dynamic coarsening method in Klemetsdal et al (2019b), and the efficiency of LRNTS has been demonstrated for black oil and compositional simulations in Klemetsdal et al (2019bKlemetsdal et al ( , 2019d. All results reported in the following are based on a proofof-concept implementation in the MRST (Lie 2019). This implementation will be included in a future release of the MRST.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Injected water into a reservoir aims to provide pressure support to the reservoir which is called voidage replacement, and to displace or drive oil from the reservoir to production wells. Water flooding performance assessment has been widely investigated in both experimental [1][2][3][4][5] and detailed numerical simulation [6][7][8][9][10] frameworks. Numerical modeling of water flooding recovery performance can be carried out with traditional simulators.…”
Section: Introductionmentioning
confidence: 99%